PLACE AND ROLE OF PSYCHOLOGICAL AND VOLITIONAL TRAININGIN THE TRAINING PROCESS OF STUDENTS-BOXERS - Muratov Muzaffar Shermamatovich; Sattarov Karshiboy Norkulovich; Hayitova Ulfatoy Tursunovna (Scholar Express Journals, 2022)
Psychological and volitional training of boxers is an essential component of an athlete's training, which ensures the achievement of high results. The article discusses the factors influencing the process of this training of a boxer.
Keywords: Boxer; Psychological And Volitional Training; Training Process; Coach